Webinar on Enhancing Technological Literacy in Education: Adapting to Rapid Technological Advancements - Dedi Rahman Nur; Abdul Rohman; Godefridus Bali Geroda; Widi Syahtia Pane; MG. Adella kornelia Yulianti. H; Annisa Rohmah (Jurnal Abdimas Mahakam, 2025)
In the era of rapid technological advancements, education has undergone significant transformation, necessitating changes in teaching methods and skills. The International Community Service Webinar “Enhancing Technological Literacy in Education: Adapting to Rapid Technological Advancements” was organized by the Research and Community Service Institution of Universitas Widya Gama Mahakam Samarinda in collaboration with the English Education Department of Universitas Siliwangi. This event, held as a webinar via Zoom Meeting, addressed challenges in integrating digital tools into education. It was supported by Indonesian Education Share-to-Care Volunteers (IES2CV) and featured speakers from V.I. Vernadsky Crimean Federal University (Russia), Bangkokthonburi University (Thailand), Grand-Plus College of Education (Nigeria), Emilio Aguinaldo College (Philippines), and the University of Malakand (Pakistan). The program provided targeted training to equip educators and students with essential skills in utilizing digital platforms, promoting collaborative research, and comprehending digital ethics and data privacy. The primary objectives included enhancing technological proficiency, increasing access to educational resources, and fostering a culture of innovation in learning environments. A total of 756 participants enrolled in the program, comprising 364 from Indonesia and 392 from various countries, including Pakistan, China, Nigeria, India, Eswatini, Thailand, the Philippines, and Iraq. The diverse participation underscores the global importance of technological literacy in education. By bridging the gap between technological advancements and educational practices, this initiative fostered the development of a more proficient and adaptable cohort of learners, ultimately enhancing the quality of education and research in the digital era